Practical Signal and Image Processing in Clinical Cardiology - Goldberger, Jeffrey J.; Ng, Jason (Springer London : Imprint: Springer, 2010)
Modern signal and image acquisition systems used in the field of cardiology acquire, analyze, and store data digitally. Surface electrocardiography, intra-cardiac electrogram recording, echocardiograms, x-ray, magnetic resonance imaging, and computed tomography are among the modalities in the cardiology field where signal processing is applied. Digital signal processing techniques allow us to automate many of the analyses that had previously been done manually with greater precision, accuracy and speed, as well as detect features and patterns in data that may be too subtle to observe by eye. As more cardiologists are becoming more reliant on such technology, a basic understanding of digital signals and the techniques used to extract information from these signals are required.